2000
DOI: 10.1109/58.852061
|View full text |Cite
|
Sign up to set email alerts
|

An application of polarized domains in ferroelectric thin films using scanning probe microscope

Abstract: The feasibility of utilizing PZT films as future data storage media was investigated using a modified AFM. Applying voltages between a conductive AFM tip and the PZT films causes the switching of ferroelectric domains. The domains are observed using an EFM imaging technique. The experimental results and calculations revealed that the electrostatic force generated between the polarized area and the tip is a main contributor for the imaging of the polarized domains. The written features on ferroelectric films we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In 2000, Shin et al at KAIST experimented with AFM data storage on sol-gel deposited PZT. Bits were written at 14 V. Data were read back by measuring electric forces either in non-contact or contact mode [171]. Dot diameters on the order of 60-100 nm were written.…”
Section: Ferroelectric Mediamentioning
confidence: 99%
“…In 2000, Shin et al at KAIST experimented with AFM data storage on sol-gel deposited PZT. Bits were written at 14 V. Data were read back by measuring electric forces either in non-contact or contact mode [171]. Dot diameters on the order of 60-100 nm were written.…”
Section: Ferroelectric Mediamentioning
confidence: 99%
“…ultrahigh areal density. Many approaches using probe-based techniques have been brought forward (Cooper et al 1999, Vettiger et al 1999, Shin et al 2000, Bhushan and Kwak 2007a, Kwak and Bhushan 2008. Various recording techniques using thermomechanical (Mamin andRugar 1992, Vettiger et al 1999), phase change (Kado and Tohda 1995, Gidon et al 2004, Wright et al 2006, magnetic (Ohkubo et al 1991), thermomagnetic (Nakamura et al 1995, Zhang et al 2002, optical (Betzig et al 1992), electrical (Barrett and Quate 1991) and ferroelectric (Franke et al 1994, Ahn et al 1997 methods have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of scanning probe microscopes (SPM), probe-based recording technologies are being developed for ultra-high areal density. Many approaches using probe-based techniques have been brought forward (Cooper et al 1999, Shin et al 2000, Bhushan 2007). Various recording techniques using thermomechanical (Mamin andRugar 1992, Vettiger et al 1999), phase change (Kado and Tohda 1995, Gidon et al 2004, Wright et al 2006, magnetic (Ohkubo et al 1991), thermomagnetic (Nakamura et al 1995, Zhang et al 2002, optical (Betzig et al 1992), electrical (Barrett and Quate 1991) and ferroelectric (Franke et al 1994, Ahn et al 1997 methods have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%